Pemberdayaan Masyarakat Dalam Upaya Pencegahan Demam Berdarah Denque DBD Di Rt 34 Puskesmas Muara Bangkahulu - Aini, Vitratal Vika; Kadir, Sultan A; Sari, Enny Febina; Sari, Cindy Puspita; Destriana; Yusran Fauzi; Tuti Rohani; Danur Azissah; Sari, Fikitri Marya (Jurnal Pengabdian Mitra Persada, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease that is still a threat to public health in Indonesia. RT 34 Muara Bangkahulu Community Health Center is no exception. Therefore, community empowerment is an important key in efforts to prevent dengue fever. One type of infectious disease that is endemic in Indonesia is dengue fever dengue (DHF). The spread of dengue fever in Indonesia is greatly influenced by population mobility, population density, and environmental conditions such as the presence of artificial containers/places or naturally in landfills or other waste places.